Обоснование выбора тягового электродвигателя для двухпоточного электромеханического механизма поворота гусеничной машины - Зыонг, Ши Хиеп; Волонцевич, Дмитрий Олегович (НТУ "ХПИ", 2015)
Предлагается анализ основных типов электроприводов с точки зрения целесообразности их использования в двухпоточном электромеханическом механизме поворота гусеничной машины. Сделан вывод о том, что для указанного электропривода, работающего в жестко нестационарных, повторно-кратковременных режимах, с диапазоном скоростей от отрицательных до превышающих значение синхронной скорости, испытывающего значительные кратковременные перегрузки в сочетании с ударными перегрузками по ускорениям, связанные с движением машины по пересеченной местности, наиболее целесообразно использовать трехфазный асинхронный электродвигатель с преобразователем частоты источника питания.

The analysis of the main types of electric drives from the point of view of expediency of their use in the two-line electromechanical mechanism of turn of the track laying vehicle is offered. It is known that the specified electric drive works in rigidly non-stationary,repeated and short-term modes, demands exact and smooth regulation of speed. The anchor of the electric motor can rotate opposite to the speed of rotation of a magnetic field aside or exceed value of synchronous speed. The drive at operation tests the considerable short-term overloads in combination with shock overloads on accelerations connected with the movement of the car on a cross-country terrain. In this regard, the conclusion that for the specified electric drive, it is most expedient to use the three-phase asynchronous electric motor with the power supply frequency converter is drawn.
Justification of a choice of the traction electric motor for the two-line electromechanical mechanism of turn for the track laying vehicle
Keywords: электропривод; гусеничный транспортер-тягач; КПД; диапазон скоростей; electric drive